Plant Origin, but Not Phylogeny, Drive Species Ecophysiological Response to Projected Climate - Münzbergová, Zuzana; Kosová, Veronika; Schnáblová, Renáta; Rokaya, Maan; Synková, Helena; Haisel, Daniel; Wilhelmová, Nada; Dostálek, Tomáš (Frontiers in Plant Science, 2020)
Knowledge of the relationship between environmental conditions and species traits is an important prerequisite for understanding determinants of community composition and predicting species response to novel climatic conditions. Despite increasing number of studies on this topic, our knowledge on importance of genetic differentiation, plasticity and their interactions along larger sets of species is still limited especially for traits related to plant ecophysiology. We studied variation in traits related to growth, leaf chemistry, contents of photosynthetic pigments and activity of antioxidative enzymes, stomata morphology and photosynthetic activity across eight Impatiens species growing along altitudinal gradients in Himalayas cultivated in 3 different temperature regimes and explored effects of among species phylogenetic relationships on the results. Original and target climatic conditions determine trait values in our system. The traits are either highly plastic (e.g. APX, CAT, plant size, neoxanthin, β-carotene, chlorophyll a/b, DEPSC) or are highly differentiated among populations (stomata density, lutein production). Many traits show strong among population differentiation in degree of plasticity and direction in response to environmental changes. Most traits indicate that the species will profit from the expected warming. This suggests that different processes determine the values of the different traits and separating the importance of genetic differentiation and plasticity is crucial for our ability to predict species response to future climate changes. The results also indicate that evolution of the traits is not phylogenetically constrained but including phylogenetic information into the analysis may improve our understanding of the trait-environment relationships as was apparent from the analysis of SLA.